Implementasi Putusan PKPU Oleh Pengadilan Niaga terhadap Pihak yang Masih dalam Sengketa Keperdataan - Christian, Ronald; Hasibuan, Fauzie Yusuf; Hakim, Nur (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This thesis aims to: 1) Analyze and examine the legal basis of the Commercial Court in deciding Suspension of Debt Payment Obligation (PKPU) cases involving debtors still engaged in civil disputes in the District Court. 2) Analyze and examine the legal certainty for debtors whose PKPU is granted, particularly regarding agreements still subject to civil disputes outside the PKPU process. This study employs normative legal research, connecting the research with prevailing laws and regulations. The findings of this thesis are: 1) The judicial considerations in Decision No. 45/Pdt.Sus-PKPU/2023/PN Niaga Mdn embrace the principle of simple proof despite the complexity of debts involved in civil disputes. This decision demonstrates that, unlike bankruptcy, PKPU aims for swift debt restructuring and peaceful settlement. This is reflected in the judge's rejection of in personam disqualification and absolute competence exceptions, alongside the affirmation of the "Lex Specialis Derogat Lex Generalis" principle. The core of the judge's consideration involves a flexible interpretation of "simply proven debt" (Article 8 paragraph (4) of the Bankruptcy Law), accepting complex contractual debts through implied admission, and utilizing final and binding court decisions as strong evidence. The legal implications of this ruling include setting aside detailed civil disputes for the sake of PKPU speed and strengthening creditor protection, thereby establishing a pro-restructuring precedent, despite potentially creating future conflicts of norms or overlapping jurisdictions. In this case, the Commercial Court functions as a "gateway" to debt restructuring, rather than a forum for in-depth substantive dispute resolution. 2) PKPU Decision No. 45/Pdt.Sus-PKPU/2023/PN Niaga Mdn provides pragmatic legal certainty for debtors amidst civil disputes, emphasizing the objective of expedited debt restructuring as opposed to bankruptcy liquidation. The Commercial Court consistently rejects formal exceptions and upholds its absolute jurisdiction based on the "Lex Specialis Derogat Lex Generalis" principle. The essence of the decision lies in a flexible interpretation of "simply proven debt" (Article 8 paragraph (4) of the Bankruptcy Law), accepting complex debts from valid agreements through implied admission, and recognizing final and binding court decisions as strong evidence. This indicates that the Commercial Court sidesteps detailed civil disputes for procedural efficiency. Consequently, this ruling strengthens creditor protection and fosters a pro-restructuring precedent, although it might lead to potential conflicts of norms if underlying disputes are decided differently in the future. The role of the Administrator and Supervisory Judge is crucial in ensuring procedural fairness. Overall, the Commercial Court serves as a "gateway" for restructuring, rather than an in-depth substantive dispute resolution forum.